Psychoanalysis of the doctrine of acute pneumonia - Igor Klepikov (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2021)
It is difficult to predict how the founder of psychoanalysis, Sigmund Freud, would react to an attempt to link his theory and the method of treating mental disorders based on it [1] with such a purely physical disease as Acute Pneumonia (AP). It is unlikely that such an innovation could cause full approval and support. However, in this context, we are not talking about psychoanalysis as a therapeutic method for AP. In this case, only the diagnostic features of this technique are of interest. The essence of psychoanalysis, which is based on the search for the causes of the so-called echoes of the past, as well as the connection between conscious and unconscious phenomena, can be useful in order to understand the causes of errors and paradoxes that exist in solving the problem of AP. In other words, we are not talking about the nuances of the disease itself, but about the peculiarities of its nature, since the interpretation of the essence of AP determines the principles of treatment and the final results.